2021
DOI: 10.3390/biom11020288
|View full text |Cite
|
Sign up to set email alerts
|

A Targeted and Tuneable DNA Damage Tool Using CRISPR/Cas9

Abstract: Mammalian cells are constantly subjected to a variety of DNA damaging events that lead to the activation of DNA repair pathways. Understanding the molecular mechanisms of the DNA damage response allows the development of therapeutics which target elements of these pathways. Double-strand breaks (DSB) are particularly deleterious to cell viability and genome stability. Typically, DSB repair is studied using DNA damaging agents such as ionising irradiation or genotoxic drugs. These induce random lesions at non-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…CRISPR/Cas system has been applied in basic research of bioengineering due to its high accuracy and short operation time (Wege et al, 2021;Zhu et al, 2020;Wright et al, 2016;Barrangou and Doudna., 2016), which can be designed to induce DSB at any genomic site (Gaj et al, 2013;Martin et al, 2012;Maeder et al, 2008;Miller et al, 2010;Claudio et al, 2011). Ioannis Emmanouilidis's research shows that the average transfection rate is up to 60% when electroporation is performed using recombinant Cas9 instead of traditional transfection (Emmanouilidis et al, 2021). In our present study, the electroporation transformation method improved the transformation efficiency and reduced the probability of false positives.…”
Section: Discussionmentioning
confidence: 54%
“…CRISPR/Cas system has been applied in basic research of bioengineering due to its high accuracy and short operation time (Wege et al, 2021;Zhu et al, 2020;Wright et al, 2016;Barrangou and Doudna., 2016), which can be designed to induce DSB at any genomic site (Gaj et al, 2013;Martin et al, 2012;Maeder et al, 2008;Miller et al, 2010;Claudio et al, 2011). Ioannis Emmanouilidis's research shows that the average transfection rate is up to 60% when electroporation is performed using recombinant Cas9 instead of traditional transfection (Emmanouilidis et al, 2021). In our present study, the electroporation transformation method improved the transformation efficiency and reduced the probability of false positives.…”
Section: Discussionmentioning
confidence: 54%
“…While CRISPR-Cas9-induced DDR with gRNAs that have multiple on-target sites has been shown previously, 16 a much more challenging task that is relevant for deploying CRISPR in the clinic is comparing the DDR effects of gRNAs with only a single on-target site characterized by low levels of DSBs. Since CRISPR-Cas9 is known to elicit a DDR, 46 which is thought to be at least partially due to off-target activity, it is critical to identify a gRNA with the most specific editing possible.…”
Section: Resultsmentioning
confidence: 96%
“…Repair-center clusters manifest as foci under the microscope, 12 , 13 facilitating quantification of DNA damage caused by gamma irradiation, zinc-finger nucleases (ZFNs), 14 , 15 and extremely promiscuous CRISPR gRNAs. 16 …”
Section: Introductionmentioning
confidence: 99%
“…The most comprehensive studies of chromatin mobility to date have been those associated with DNA damage. DNA (Emmanouilidis et al, 2021;Wang et al, 2019) or genotoxic agents such as zeocin or bleomycin, or c radiation. In different model species, it has been shown that, subsequent to DSBs, chromatin becomes generally more mobile (Dion et al, 2012;Dion et al, 2013;Hauer et al, 2017;Herbert et al, 2017;Lawrimore et al, 2017;Min e-Hattab et al, 2017;Min e-Hattab & Rothstein, 2012;Strecker et al, 2016).…”
Section: Chromatin Mobility During Dna Repairmentioning
confidence: 99%